2017
DOI: 10.1371/journal.pone.0186892
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of equine botulism antitoxin in Rhesus macaques

Abstract: BackgroundThere are currently no licensed vaccines available for prevention of botulism in humans. The vaccination is not desirable due to expanding therapeutic indications of botulinum toxins. The only available specific treatment for botulism is antitoxin to remove circulating toxin, thus, preventing further neuronal damage. BAT® (Botulism Antitoxin Heptavalent (A, B, C, D, E, F, G)—(Equine)) has been developed and its therapeutic efficacy evaluated against botulinum neurotoxin serotype A (BoNT/A) in Rhesus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 58 publications
(65 reference statements)
2
38
0
Order By: Relevance
“…Almost all animals treated at 24 h postexposure (14 IU/kg antitoxin or higher) survived, whereas even a 30-fold-higher antitoxin dose failed to confer any protection when administered at the first signs of disease (39). However, in another recent rhesus macaque study, different results were obtained, as treatment with HBAT after the onset of clinical signs following intravenous exposure to BoNT/A (1.7 LD 50 ) conferred partial protection (46% survival) (42).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Almost all animals treated at 24 h postexposure (14 IU/kg antitoxin or higher) survived, whereas even a 30-fold-higher antitoxin dose failed to confer any protection when administered at the first signs of disease (39). However, in another recent rhesus macaque study, different results were obtained, as treatment with HBAT after the onset of clinical signs following intravenous exposure to BoNT/A (1.7 LD 50 ) conferred partial protection (46% survival) (42).…”
Section: Discussionmentioning
confidence: 95%
“…As a consequence, the use of antitoxin in animal studies has been related mostly to time postintoxication, whereas data regarding treatment after the onset of symptoms have been collected only post factum (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). To the best of our knowledge, only a few attempts to directly measure postsymptom antitoxin efficacy were reported, mostly for BoNT/A-intoxicated nonhuman primates (14,(39)(40)(41)(42). In those studies, as in all other animal models reported thus far, symptoms were based on subjective observations, and therefore, their onset might not be witnessed precisely and may vary substantially among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we test the hypothesis that 3,4-DAP improves respiratory and skeletal muscle paralysis in vivo at clinically relevant time points after exposure to BoNT serotypes A, B, and E. These studies were conducted in mice intoxicated with up to 5 LD 50 of toxin. Based on correlation of the rate of disease progression between nonhuman primates and clinical patients, 5 LD 50 is estimated to represent an upper range for typical human foodborne exposure to serotypes A, B, or E (44,45). We found that human-equivalent doses of 3,4-DAP reversed limb and respiratory paralysis caused by each BoNT serotype.…”
Section: Introductionmentioning
confidence: 85%
“…Clinical severity scoring (CSS) was conducted by at least 3 blinded participants. A CSS rubric used in guinea pigs and nonhuman primates was modified to remove ptosis and hypersalivation, which are either absent or difficult to reliably measure in mice (44). The resulting modified CSS rubric was (scores are cumulative): mild abdominal paradox (score of 1), moderate abdominal paradox (score of 2), severe abdominal paradox and/or agonal respiratory pattern (score of 3), lethargy (score of 1), generalized body weakness (score of 2), total body paralysis (lack of righting reflex, score of 3), or death (16).…”
Section: Methodsmentioning
confidence: 99%
“…In most reported botulism animal studies aimed at evaluating postexposure treatment efficacy, antitoxin was administered in a time postexposure mode. Only a few attempts have been made to study PSAE ( Adler and Franz, 2016 ; Dack and Wood, 1928 ; Kodihalli et al, 2017 ; Oberst et al, 1968 ; Food and Drug Administration BAT ® Data Sheet, ). Moreover, symptoms in these studies were limited to those that can only be noticed by simple observation.…”
Section: Discussionmentioning
confidence: 99%